STUDENTS PERCEPTION TOWARDS THE APPLICATION OF GRAMMARLY: THE AUTOMATIC GRAMMAR CHECKER IN WRITING NARRATIVE TEXT IN THE THIRD SEMESTER AT STKIP YPUP MAKASSAR - Vitalis Tarsan; Antonius Kandang; Arnoldus Helmon (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
One aspect that needs to be considered in writing narrative texts is grammar. Mastery of grammar, for language learners, is very important especially in writing narrative texts. One of the web applications that can help academics and language learners, in checking language, especially grammar in narrative text writing, is the automatic grammar checker. An automatic grammar checker is a web application that can check the grammar in a written work. This research was to determine student perceptions of Grammarly application in checking grammar in writing narrative texts. The approach used to describe the focus of this research is a qualitative approach. This research was conducted in July 2019. The population of this research was the third-semester students of English Education the Department, STKIP YPUP Makassar, in the 2018/2019 school year. The total number of the population is 90 students. To get the research sample, the researcher used the purposive sampling technique. The research sample amounted to 10 people. Data collection techniques used in this research are technical tests and filling out questionnaires. The reason of researcher used technical tests and filling out questionnaires so that data more representative, valid, and accurate. There are two questionnaires used by the researcher in this research, namely the first open-ended questions and the second closed question. After the data was collected, the researcher then analyzed the data. The process of data analysis: checked and read the result of questionnaires, analyzed and reduced questionnaire data descriptive, and finally describe data and information in the form of the final report on the research result In this research, it was found that students had a positive perception of using the Grammarly application to check grammar in writing narrative texts. The respondents said that they strongly agree to use the Grammarly application in checking grammar in their narrative text writing. They are very satisfied with the quality of this application in checking the grammar in their writing.